2020
DOI: 10.1038/s41467-020-18038-y
|View full text |Cite
|
Sign up to set email alerts
|

Ecological uncertainty favours the diversification of host use in avian brood parasites

Abstract: Adaptive responses to ecological uncertainty may affect the dynamics of interspecific interactions and shape the course of evolution within symbioses. Obligate avian brood parasites provide a particularly tractable system for understanding how uncertainty, driven by environmental variability and symbiont phenology, influences the evolution of species interactions. Here, we use phylogenetically-informed analyses and a comprehensive dataset on the behaviour and geographic distribution of obligate avian brood par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 72 publications
(91 reference statements)
1
27
0
Order By: Relevance
“…Eye size did not differ significantly for the phylogenetic regression model ( β = 0.002, p = 0.99), likely because brood parasitism has independently evolved only within a handful of avian families ( N = 7 origins, e.g. [ 2 ]). Hosts had significantly smaller eyes than non-hosts for both non-phylogenetic ( β = −0.11, p < 0.001) and phylogenetic models ( β = −0.02, p < 0.02).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eye size did not differ significantly for the phylogenetic regression model ( β = 0.002, p = 0.99), likely because brood parasitism has independently evolved only within a handful of avian families ( N = 7 origins, e.g. [ 2 ]). Hosts had significantly smaller eyes than non-hosts for both non-phylogenetic ( β = −0.11, p < 0.001) and phylogenetic models ( β = −0.02, p < 0.02).…”
Section: Resultsmentioning
confidence: 99%
“…We sourced host status, the identities of host-specific parasites, and egg rejection rates for hosts of obligate avian brood parasites also from previously published databases [ 2 , 12 , 26 ]. This information was then annotated regarding whether the respective parasite laid an avian-perceived mimetic or non-mimetic egg as modelled by the particular host's visual system [ 16 , 27 ] and indicated by the respective spectral and perceptual review literature (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Low heterogeneity in resources exchanged by partners can result in opportunistic interactions (Pinheiro et al, 2019). A recent study also showed that high ecological uncertainty can favor generalized host ranges in avian brood parasites (Antonson et al, 2020). How and when selection maintains the variation necessary for opportunistic interactions is not fully understood (Vamosi et al, 2014; but see Batstone et al, 2018), but it seems to be pervasive even in highly intimate symbioses such as lichens and corals (Fig.…”
Section: A Conceptual Framework For An Eco-evolutionary Interpretation Of Pss Valuesmentioning
confidence: 99%